2016
DOI: 10.1111/een.12298
|View full text |Cite
|
Sign up to set email alerts
|

Measuring floral resource availability for insect pollinators in temperate grasslands – a review

Abstract: Abstract. 1. The relationship between pollinators and flowering plants plays a crucial role in the function of terrestrial ecosystems. Although pollinators use floral nectar and pollen as food resources, no general methodology for floral resource availability estimates exists.2. A brief review is provided on floral resource sampling methods frequently used in pollination studies. The focus is on how representative vegetation samples are both spatially and temporally, and how these are constrained by sampling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Most field studies reviewed by Szigeti et al (2016) measure floral resource availability to investigate the relationship between resource availability and pollinator population size or diversity (e.g. Kovács-Hostyánszki et al 2013); the relationship between resource availability and flower preferences (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most field studies reviewed by Szigeti et al (2016) measure floral resource availability to investigate the relationship between resource availability and pollinator population size or diversity (e.g. Kovács-Hostyánszki et al 2013); the relationship between resource availability and flower preferences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Currently no generally accepted methodology exists to estimate floral resource availability . Although there is a vast amount of studies investigating plant sampling protocols for botanical studies, including the comparison and evaluation of different methods (Walker 1970;Everson & Clarke 1987;Vittoz & Guisan 2007;Symstad et al 2008), recommendations on how to measure floral resource availability for pollinators are scarce, and rather different methods have been applied to estimate resource availability (Frankl et al 2005;Hicks et al 2016;Szigeti et al 2016). Some studies neglect or do not refer to existing vegetation sampling protocols or the description of methodology is insufficient ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several commercial seed mixes have been designed and are available to support and enhance beneficial arthropod communities. Although floral resources are being implemented, there exist few quantifiable measurements of how much area to plant in a landscape, and what will be the resulting effect of different quantities of floral resources for promoting beneficial arthropod populations [43]. The use of UAVs has increased dramatically in recent years, and they appear to be a feasible approach for assessing floral resources in agricultural landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extracting random samples of an area to estimate floral resources available would be the preferred method for large scale implementation. For manual counts, observer bias [43,47] is an issue, especially with the large teams that would be needed to document floral resource availability at large spatial extents. Results suggested that the number of pollinators in a given area can be indirectly predicted by the amount of floral area estimated in a landscape, and sampled using a UAV with a simple RGB camera.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological, morphological and phylogenetic investigations pertaining to nectar chemistry have received considerable attention (Szigeti et al . ). Several methods exist to sample floral nectar in the field, including microcapillary pipettes, syringes and graduated pipettes (Kearns & Inouye ; Corbet ), paper wicks (McKenna & Thomson ; Castellanos et al .…”
Section: Introductionmentioning
confidence: 97%